Pengembangan Sistem Komunikasi Nirkabel Untuk Mengendalikan Robot Sepak Bola - Alfa Satya Putra; Arnold Aribowo; Hendra Tjahyadi (Jurnal RESTI (Rekayasa Sistem dan Teknologi Informasi), 2018)
According to how soccer robot movement is controlled, approaches in soccer robot can be divided into two categories, namely centralized and decentralized. Centralized approach is an example of control over network concept where devices are controlled over the network. Each robot obtains information from a vision system outside the robot to detect the ball, and the central computer makes decision on which robot to approach and kick the ball. Wireless communication between robot and central computer must be reliable. One of the most important components in soccer robot is the ball kicking mechanism, which has to be able to kick the ball accurately. The wireless communication system is developed with a WeMos D1 microcontroller. Ball kicking mechanism is developed using solenoid circuit controlled by the microcontroller. Testing showed that wireless communication system has 100% reliability when operated in range up to 300cm. The ball kicking mechanism was able to respond accurately to ball kicking command when the robot is stationary and moving. When the robot is stationary, average kicking distance of the ball is 42.22cm and average tilt angle is 29.58°. When robot is moving, average kicking distance is 40.98cm and average tilt angle is 26.12°.